2016
DOI: 10.3389/fmicb.2016.01048
|View full text |Cite
|
Sign up to set email alerts
|

Mississippi River Plume Enriches Microbial Diversity in the Northern Gulf of Mexico

Abstract: The Mississippi River (MR) serves as the primary source of freshwater and nutrients to the northern Gulf of Mexico (nGOM). Whether this input of freshwater also enriches microbial diversity as the MR plume migrates and mixes with the nGOM serves as the central question addressed herein. Specifically, in this study physicochemical properties and planktonic microbial community composition and diversity was determined using iTag sequencing of 16S rRNA genes in 23 samples collected along a salinity (and nutrient) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 40 publications
8
40
1
Order By: Relevance
“…This is consistent with the previous study of Mason et al. (), who reported that the Mississippi River enhances bacterial diversity in the Gulf of Mexico.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is consistent with the previous study of Mason et al. (), who reported that the Mississippi River enhances bacterial diversity in the Gulf of Mexico.…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, our results indicated that river run-off markedly enhanced fungal OTU richness, as highlighted by the significantly higher OTU richness in CWM-influenced sediment (Figure 3a). This is consistent with the previous study of Mason et al (2016), who reported that the Mississippi River enhances bacterial diversity in the Gulf of Mexico.…”
Section: This Clear Transition In Fungal Communities From Costal To Osupporting
confidence: 94%
“…Together, these factors cause bacteria to have a short residence time in surface waters. However, similar to the results shown in large estuaries [7,19,20], the bacterial communities of the Estuary of Bilbao were classified in two large groups according to salinity: brackish-euhaline communities (salinity > 5 ppt) and freshwater communities (salinity < 5 ppt) (Fig 4). Accordingly, the Spearman correlation values between OTUs and environmental features showed highest rho values when testing for salinity (rho = 0.72–0.85 for salinity and rho = 0.52–0.64 for temperature, S2 and S4 Tables).…”
Section: Discussionsupporting
confidence: 81%
“…The geomorphology of the Estuary of Bilbao contrasts to that of large estuaries characterized to date through amplicon sequencing (Mississippi [19], Sydney [20], etc.). The Estuary of Bilbao is short (~20 km) with low river discharge (max = 37 m 3 s -1 ) and a contrasting tidal fluxing rate (max = 700 m 3 s -1 in the outer zone and max = 10 m 3 s -1 in the inner zone) [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation